Institution of an antibiotic stewardship programme for rationalising antibiotic usage: a quality improvement project in the NICU of a public teaching hospital in rural central India. (3rd August 2021) - Jain, Manish; Bang, Akash; Meshram, Payal; Gawande, Prachi; Kawhale, Karuna; Kamble, Pushpanjali; Deotale, Vijayshri; Datta, Vikram; Dhanireddy, Ramasubbareddy
Abstract : Antibiotic misuse is the most common cause of antimicrobial resistance—a globally declared emergency. This necessitates the introduction of rational antibiotic usage management policy. The paediatrics department of a public teaching hospital with around 500 neonatal intensive care unit (NICU) admissions annually revealed 75% of NICU admission exposure to any antibiotics. The aim was to institute antibiotic stewardship programme (ASP) to optimise antibiotic usage from existing 75% to 40% in a 6-month period through a quality improvement (QI) project.A root cause analysis using fishbone diagram was performed to identify the possible reasons for the high antibiotic usage. Six Plan-Do-Study-Act cycles were conducted to implement the protocols for usage of antibiotics for well-defined indications; active laboratory engagement to decrease the turnaround time for blood culture results; a hard stop to all antibiotic orders after 72 hours; streamlining of antibiotic usage; strengthening universal aseptic practices; and confidence building of staff. The outcomes monitored were antibiotic exposure rates, average number of antibiotic days in all NICU admissions, sepsis rates and mortality.Institution of ASP had significantly reduced antibiotic exposure in NICU admissions, that is, from 75% in March to 41% in August 2018. Median (IQR) antibiotic days per infant in NICU went down from 3 to 0 (0–6). The per cent of NICU admission with culture-positive sepsis and all-cause mortality rate in NICU declined from 18% to 11.56% and 25% to 16%, respectively, over these 6 months.Thus, ASP for rationalising antibiotic usage was successfully instituted in NICU of a rural medical college in central India through QI, without any adverse effect on sepsis and mortality.